Hubungan Kekuatan Otot Lengan Terhadap Ketepatan Servis Atas Atlet Bola Voli Putra Kota Madiun - Darumoyo, Kuncoro; Setyo Nugroho, Gunung; Nur Wahyudi, Arief (Jurnal Porkes, 2024)
The problem in this study is the strength of the arm muscles to the accuracy of the service over the volleyball game is very lacking in the game. This researcher aims to examine the relationship between arm muscle strength and the accuracy of the upper serve of Madiun City male volleyball athletes. This study uses a type of correlational research. The method used is quantitative, with data collection techniques using tests and measurements. The population in this study were Madiun City male volleyball athletes, totaling 13 athletes. Determining the sample using probability sampling technique with saturated sampling method. Instruments to measure arm muscle strength using the push-up test, and upper service ability using the volleyball service test from AAHPERD. Data analysis using Pearson product moment correlation with the help of SPSS application. The results of the product moment correlation test obtained a sig value. 0.000 < 0.05 while the person correlation value is 0.863 > 0.05, it can be concluded that the relationship between arm muscle strength and the accuracy of volleyball top serves has a significant relationship.